Determinants of Increased Effort of Breathing in Non-Intubated Critical COVID-19 Patients - Vaidas Vicka; Elija Januskeviciute; Justina Krauklyte; Aiste Aleknaviciene; Donata Ringaitiene; Ligita Jancoriene; Jurate Sipylaite (Medicina, 2022)
Background and objectives: Acute respiratory distress syndrome (ARDS) is the most common complication occurring in COVID-19 patients admitted to the ICU. Given the increased respiratory work of these patients, it is necessary to evaluate their actual breathing efforts. The aim of this study is to report the incidence and determinants of increased effort of breathing (EOB) in critical COVID-19 patients. Materials and Methods: This was a retrospective study of COVID-19 patients admitted to the ICU during the year of 2020. Respiratory rate (RR) was chosen as an indicator of EOB. The cut-off value was set at more than 20 breaths per minute. ROC-AUC analysis was performed to identify the accuracy of the PaO2 and PaCO2 to determine increased EOB. Furthermore, multivariate regression analysis was performed to reveal the determinants of increased EOB. Results: 213 patients were included in the study. Mean RR in the population was 24.20 ± 6.28. 138 (64.8%) of the patients had increased EOB. The ROC-AUC analysis revealed the PaO2 (0.656 (CI 95%: 0.579–0.734, p < 0.001) as more accurate predictor of EOB than PaCO2 (0.584 (CI 95%: 0.505–0.662, p = 0.043). In the final multivariate model, the SpO2 (exp(B) = 0.922, CI 95%: 0.874–0.97 p = 0.033), PaO2/FiO2 ratio (exp(B) = 0.996, CI 95%: 0.922–1.000, p = 0.003) and PaO2 (exp(B) = 0.989 CI 95%: 0.982–0.996 p = 0.003) prevailed as independent predictors of increased EOB. Conclusions: To conclude, PaO2 was revealed as a more accurate predictor of increased EOB than PaCO2. Further investigation revealed the independent determinants of EOB: blood oxygen saturation, PaO2 and PaO2/FiO2 ratio.